Population Genetics And Molecular Taxonomy Of Two Important Cultured Oyster Species In Malaysia, Crassostrea iredalei (Faustino, 1932) And C. belcheri (Sowerby, 1871) - Mustaffa, Suzana (2011)
A total of 140 Crassostrea iredalei (Faustino 1932) and 83 C. belcheri (Sowerby 1871) samples were analysed from 16 locations along the coast of Malaysia. Genetic diversities were assessed using a 581-nucleotide fragment of the mtDNA cytochrome oxidase subunit 1 (COI) gene. FST and AMOVA analyses generally structured C. iredalei samples into two major groups, consistent with their geographic origins in mainland Peninsular Malaysia and Malaysian Borneo (Sabah). In C. belcheri, FST analysis showed that the Tawau population was differentiated from the rest including the other Sabah population of Sandakan.